DINAMIKA KERAGAAN KEMISKINAN DI DESA PATANAS DAN UPAYA MENGATASINYA - Valeriana Darwis (Universitas Sebelas Maret, 2014)
Poverty reduction is a priority development agenda and a lot of programs or policies that have been implemented by the government. One of the pockets of poverty are diperdesaan where people work in the agricultural sector. In locations irrigated rice agro-ecosystem study the performance of rice-based poverty in 2007 and 2010 experienced a negative growth, it is seen from: (i) reduced employment and increased unemployment, (ii) a source of income from agriculture generally, but she became a source of income in non-agriculture, (iii) land ownership between 0.25 to 1 ha and reverse the decline of arable land rent is increasing, (iv) expenditure on food increased primarily to meet the needs of carbohydrates and animal sources. The dynamics of the most positive efforts made respondents in addressing the problem of food by way of debt, overcoming difficulties by reducing the amount of clothing purchases, overcoming difficulties fulfilling its way into participants health insurance for the poor, addressing educational problems by borrowing money or do not attend school.